2020
DOI: 10.3329/bjpt.v27i1.47580
|View full text |Cite
|
Sign up to set email alerts
|

Utricularia geminiscapa Benj. (Lentibulariaceae): A new angiospermic record for Bangladesh

Abstract: not available Bangladesh J. Plant Taxon. 27(1): 191-194, 2020 (June)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In Bangladesh, the endeavour of exploring new plant species is continuing, and as a consequence, the taxonomists of this country have published a notable number of new records in the last few decades, though sporadically. Likewise, after the publication of the Encyclopedia of the Flora and Fauna of Bangladesh (EFFB) (Ahmed et al 2008(Ahmed et al -2009(Ahmed et al , 2009Siddiqui et al 2007), around 281 new records of Angiosperms have been published, mostly with information on the specific distribution of the recorded taxa (Rahman and Hassan, 2017;Islam and Rahman, 2017;Sourav et al, 2017;Ara and Hassan, 2018;Rahman and Uddin, 2018;Uddin, 2018;Alfasane et al, 2019Alfasane et al, , 2020Hossain et al, 2020;Sultana and Rahman, 2021;Hossain et al, 2022;Rahman et al, 2022;Sultana et al, 2022;Uddin and Uddin, 2022). It means that in the last 13 years, around 7.78% of the EFFB's record of 3611 species and 5.6% of Khan (1977)'s estimate of 5000 species of Angiosperms to exist within the territory of Bangladesh have been newly added to the flora of this country.…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, the endeavour of exploring new plant species is continuing, and as a consequence, the taxonomists of this country have published a notable number of new records in the last few decades, though sporadically. Likewise, after the publication of the Encyclopedia of the Flora and Fauna of Bangladesh (EFFB) (Ahmed et al 2008(Ahmed et al -2009(Ahmed et al , 2009Siddiqui et al 2007), around 281 new records of Angiosperms have been published, mostly with information on the specific distribution of the recorded taxa (Rahman and Hassan, 2017;Islam and Rahman, 2017;Sourav et al, 2017;Ara and Hassan, 2018;Rahman and Uddin, 2018;Uddin, 2018;Alfasane et al, 2019Alfasane et al, , 2020Hossain et al, 2020;Sultana and Rahman, 2021;Hossain et al, 2022;Rahman et al, 2022;Sultana et al, 2022;Uddin and Uddin, 2022). It means that in the last 13 years, around 7.78% of the EFFB's record of 3611 species and 5.6% of Khan (1977)'s estimate of 5000 species of Angiosperms to exist within the territory of Bangladesh have been newly added to the flora of this country.…”
Section: Introductionmentioning
confidence: 99%
“…The flora of Bangladesh comprises a total of 3873 species of Angiosperms including 262 new records (Haque et al, 2012;Rahman et al, 2016;Rahman and Hassan, 2017;Islam and Rahman, 2017;Sourav et al, 2017;Ara, 2018;Ara and Hassan, 2018;Islam et al, 2018;Uddin et al, 2018;Uddin 2018;Alfasane et al, 2019Alfasane et al, , 2020Hossain et al, 2019;Huda et al, 2019) reported so far after the publication of Encyclopedia of Flora and Fauna of Bangladesh by Siddiqui et al (2007Siddiqui et al ( -2008 and Ahmed et al (2008Ahmed et al ( -2009.…”
Section: Introductionmentioning
confidence: 99%
“…So far known, the freshwater Lentibulariaceae of Bangladesh is represented by nine species, namely Utricularia aurea Lour., U. bifida Linn., U. caerulea Linn., U. foliosa L., U. geminiscapa Benj., U. gibba Linn., U. inflexa Forsk., U. minutissima Vahl, and U. scandens Benj. (Hooker, 1888;Prain, 1903;Datta and Mitra, 1953;Khan and Halim, 1987;Uddin et al, 2000;Rahman, 2005;Ahmed, 2009;Alfasane et al, 2020).…”
Section: Introductionmentioning
confidence: 99%